# Biconditional as Disjunction of Conjunctions/Formulation 2/Proof 1

Jump to navigation
Jump to search

## Theorem

- $\vdash \paren {p \iff q} \iff \paren {\paren {p \land q} \lor \paren {\neg p \land \neg q} }$

## Proof

By the tableau method of natural deduction:

Line | Pool | Formula | Rule | Depends upon | Notes | |
---|---|---|---|---|---|---|

1 | 1 | $p \iff q$ | Assumption | (None) | ||

2 | 1 | $\paren {p \land q} \lor \paren {\neg p \land \neg q}$ | Sequent Introduction | 1 | Biconditional as Disjunction of Conjunctions: Formulation 1 | |

3 | $\paren {p \iff q} \implies \paren {\paren {p \land q} \lor \paren {\neg p \land \neg q} }$ | Rule of Implication: $\implies \II$ | 1 – 2 | Assumption 1 has been discharged | ||

4 | 4 | $\paren {p \land q} \lor \paren {\neg p \land \neg q}$ | Assumption | (None) | ||

5 | 4 | $p \iff q$ | Sequent Introduction | 4 | Biconditional as Disjunction of Conjunctions: Formulation 1 | |

6 | $\paren {\paren {p \land q} \lor \paren {\neg p \land \neg q} } \implies \paren {p \iff q}$ | Rule of Implication: $\implies \II$ | 4 – 5 | Assumption 4 has been discharged | ||

7 | $\paren {p \iff q} \iff \paren {\paren {p \land q} \lor \paren {\neg p \land \neg q} }$ | Biconditional Introduction: $\iff \II$ | 3, 6 |

$\blacksquare$